To solve the system of equations using the elimination method, we have:
- \( y = x^2 - 2x - 2 \)
- \( y = 2x - 6 \)
Since both equations are equal to \( y \), we can set them equal to each other:
\[ x^2 - 2x - 2 = 2x - 6 \]
Next, we will move all terms to one side of the equation:
\[ x^2 - 2x - 2 - 2x + 6 = 0 \]
Combining like terms gives us:
\[ x^2 - 4x + 4 = 0 \]
This is a perfect square trinomial that can be factored:
\[ (x - 2)^2 = 0 \]
Setting the factor equal to zero, we solve for \( x \):
\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \]
Now that we have \( x = 2 \), we can substitute this value back into one of the original equations to find \( y \). We'll use the second equation:
\[ y = 2(2) - 6 = 4 - 6 = -2 \]
So, we have the solution:
\[ (x, y) = (2, -2) \]
Next, to check if there are any other solutions, we can substitute \( x = 2 \) into the first equation:
\[ y = 2^2 - 2(2) - 2 = 4 - 4 - 2 = -2 \]
Thus, the only solution for the system is \((2, -2)\).
The final answer is:
(2, -2)